Az Orosházi kistérség középiskoláinak beiskolázásával kapcsolatos felmérés a 2011/2012-es tanévben - Zsótér, Brigitta; Kapu, Fanni Anikó (Jelenkori Társadalmi és Gazdasági Folyamatok, 2014)
Since the political transformation the Hungarian educational system has overgone many changes as an effect of the permanent modification of public education law. As a result, significant differences in performance can be observed between the different school types. The role of grammar and technical schools have increased, meanwhile the value of vocational schools has been socially reduced. We made a survey among the pupils of 9th form in the four secondary schools found in the small region of Orosháza in order to see what factors affect their choice of school. The most important factors proved to be the future plans, proximity of the living place, parents’ social position and the social conditions of the family. As a result of our research we got an overall picture of the training opportunities hidden in the region, pupils’motivation and factors which determine their choice.